«Lo que los españoles llaman la transición» - Juan Francisco Fuentes Aragonés (Mélanges de la Casa de Velázquez, 2006)
This article follows the development of the concept of transition in the history of Spain, focusing on the years 1975-1982 but also considering the «prehistory» of the concept and its subsequent evolution. Numerous accounts by witnesses were drawn upon to formulate a definition of the political phenomenon of that name taking into account the relative originality of the process that Spain lived through following the death of Franco. In fact the transition served as a model for other subsequent processes in Europe and America in the course of what Huntington called the «third wave of democratisation». The article also identifies a number of historical/semantic connections with other key concepts more or less related to the transition, such as reform, consensus, agreed rupture or disenchantment. Finally, it discusses the origin of the concept of a second transition and the political debate that has arisen around it in the last few years, and the possibility of an attempt to delegitimise the «first» transition.